2013
DOI: 10.1002/jrs.4199
|View full text |Cite
|
Sign up to set email alerts
|

The combination of surface enhanced Raman spectroscopy and an ionic liquid as a model system to study the adhesion interface between sulfur and brass

Abstract: The adhesion of steel cord to rubber is very important for the quality of reinforced rubber products, e.g. tyres. Therefore, steel cord is often plated with brass, which will lead to CuxS bonds after reaction with sulfur compounds in the rubber. A unique in‐situ analytical method has been developed to investigate the sulfur–brass interface: the sulfuring process has been simulated via a heating process in a water‐free transparent ionic liquid with added sulfur and the reaction at the brass‐coated steel cord ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…Zinc Oxide ZnO, where the location of the vibrational modes located at 105, 385, 445, 585 and 663 cm -1 are associated with the vibrational active modes of the Wurtzite phase of ZnO (Ruiz et al, 2011) the dominant peak at 445 cm -1 is attributed to high-frequency phonons from oxygen atoms (Fletcher et al, 2014), and E1 (LO) mode at 585 cm -1 is associated with interstitial zinc and oxygen vacancies, the E2 L peak at 105 cm -1 is associated with the vibrations of the zinc (Scepanovic et al, 2009), the vibrational mode E2 high -E2 low at 337 cm -1 is associated with multifononic processes (Londoño-Calderón et al, 2012) and finally the vibrational mode A 1 TO at 385 cm -1 is associated with intrinsic defects (Sundara Venkatesh et al, 2016), for the ZnS the additional presence of two resonant raman lines is observed in 217 and 350 cm -1 that correspond to the active vibrational modes of the ZnS, the spectrum shows the dominant peak in 350 cm -1 identified as a mode T2 (LO) of first order [20] (Milekhin et al, 2012), the LO mode in 217 cm -1 is attributed to the second order of raman scattering (Fairbrother et al, 2014). The heterostructure ZnO/ZnS/CuS locates the characteristic peaks that are associated with the presence of ZnO, ZnS and CuS and the appearance of the new peak that denotes the presence of the coveline phase of CuS at 165 cm -1 and 465 cm -1 (Baert et al, 2013). The photocatalytic test was performed with the degradation of MB (methylene blue), and MO (methyl orange).…”
Section: Resultsmentioning
confidence: 98%
“…Zinc Oxide ZnO, where the location of the vibrational modes located at 105, 385, 445, 585 and 663 cm -1 are associated with the vibrational active modes of the Wurtzite phase of ZnO (Ruiz et al, 2011) the dominant peak at 445 cm -1 is attributed to high-frequency phonons from oxygen atoms (Fletcher et al, 2014), and E1 (LO) mode at 585 cm -1 is associated with interstitial zinc and oxygen vacancies, the E2 L peak at 105 cm -1 is associated with the vibrations of the zinc (Scepanovic et al, 2009), the vibrational mode E2 high -E2 low at 337 cm -1 is associated with multifononic processes (Londoño-Calderón et al, 2012) and finally the vibrational mode A 1 TO at 385 cm -1 is associated with intrinsic defects (Sundara Venkatesh et al, 2016), for the ZnS the additional presence of two resonant raman lines is observed in 217 and 350 cm -1 that correspond to the active vibrational modes of the ZnS, the spectrum shows the dominant peak in 350 cm -1 identified as a mode T2 (LO) of first order [20] (Milekhin et al, 2012), the LO mode in 217 cm -1 is attributed to the second order of raman scattering (Fairbrother et al, 2014). The heterostructure ZnO/ZnS/CuS locates the characteristic peaks that are associated with the presence of ZnO, ZnS and CuS and the appearance of the new peak that denotes the presence of the coveline phase of CuS at 165 cm -1 and 465 cm -1 (Baert et al, 2013). The photocatalytic test was performed with the degradation of MB (methylene blue), and MO (methyl orange).…”
Section: Resultsmentioning
confidence: 98%
“…The most dominant modes seen at 9 PHR and 12 PHR ( Figure 4 B1,C1) of ZnO are 580, 437, and 475 cm –1 , corresponding to the E 2 and E 1 LO modes of ZnO and A 1g LO mode of CuS. 30 , 31 The chalcocite (Cu 2 S) phases identified in TEM and XRD for 9 PHR and 12 PHR are unseen in Raman as Cu 2 S is Raman inactive. 30 Confocal Raman image ( Figure S7 ) shows the appearance of the BCSC with varying ZnO concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The model system can also be used to perform electrochemical measurements at the same time. [218] Cerdeira et al use Raman spectroscopy as a probe of molecular order, orientation, and stacking of fluorinated copperphthalocyanine (F 16 CuPc) thin films. The results suggest that the thicker and most ordered film is structurally close to the recently reported crystal organization of bulk ribbon samples of this compound.…”
Section: Single Crystalsmentioning
confidence: 99%
“…Baert and coworkers show that the combination of SERS and an ionic liquid as a model system can be used to study the adhesion interface between sulfur and brass. The model system can also be used to perform electrochemical measurements at the same time . Cerdeira et al .…”
Section: Introductionmentioning
confidence: 99%